PENGARUH STRATEGI PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN TAMU MENGINAP DI HOTEL REDDOORZ NEAR HERMES PLACE POLONIA MEDAN DI MASA PANDEMI COVID-19 - Terima Jaya Harefa (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
The development of the hospitality industry in Medan has added to the increasingly intense competition between hotel companies, where each company is competing to attract consumers through superior offers compared to competitors and to retain consumers.The objective of these study are to know : (1) The effect of Promotion Strategy on guest’s decision to stay at the Hotel Reddoorz Near Hermes Place Polonia Medan In The Time Pandemy COVID-19.(2) The effect of Service Quality on guest’s decision to stay at the Hotel Reddoorz Near Hermes Place Polonia Medan In The Time Pandemy COVID-19.(3) The effect of the Influence promotion strategy andService Quality on guest’s decision to stay at the Hotel Reddoorz Near Hermes Place Polonia Medan In The Time Pandemy COVID-19.The research method that used is Quantitative Methods with descriptive analysis. The total information collected and expressed in numbers such as the number of stays in 2020.The technique of data collection that used to analyze this data by observation, interview, and distribution of questionnaires in the Hotel Reddoorz Near Hermes Place Polonia Medan In The Time Pandemy COVID-19.Result of research methodology showed that : (1) The Influence of Promotion Strategy on guest decisions to stay It was obtained TCount5,818> TTabel 1,672 with Sig a (0,000 <0,05),(2) The Service Qualityon guest decisions to stay it was obtainedTCount40,151> TTabel 1,672 with Sig a (0,008 <0,05), (3)The effect of the Influence promotion strategy andService Quality on guest’s decision to stayit was obtainedTCount181190,719 > TTabel 2,40.